Enhanced reverse zoonotic potential and immune evasion by omicron JN.1 variant - Jiaxin Hu; Fuwen Zan; Yixin He; Xiuyuan Ou; Xiaolu Tang; Yan Liu; Xing Lu; Pei Li; Zhixia Mu; Siwen Dong; Yahan Chen; Lin Tan; et al. (iScience)
Summary: SARS-CoV-2 infects not only humans but also animals, posing reverse zoonotic risks. As SARS-CoV-2 rapidly evolves, JN.1 has become dominant globally. In this study, we determined the susceptibility of XBB.1.16, EG.5.1, BA.2.86, and JN.1 to 27 different animal angiotensin-converting enzyme 2 (ACE2) orthologs using pseudoviruses, and found that JN.1 displayed substantially higher overall reverse zoonotic risk potential compared to other variants except for EG.5.1. Live virus infection experiments further confirmed higher infectivity of JN.1 than BA.2.86. Mechanistic analyses revealed that L455S might be responsible for substantial increase in overall fusogenecity and infectivity by lowering S protein thermostability. Additionally, we also found that L455S mutation enhanced immune evasion of SARS-CoV-2, and XBB breakthrough infection increased levels of neutralization antibodies against JN.1. Together, our findings offer a better mechanistic understanding of CoV entry, host range, evolution, and immunogenicity and highlight the importance of surveillance of susceptible hosts to prevent potential outbreaks.